2020
DOI: 10.2147/jmdh.s240124
|View full text |Cite
|
Sign up to set email alerts
|

<p>Practical and Cultural Barriers to Reporting Incidents Among Health Workers in Indonesian Public Hospitals</p>

Abstract: This study investigated the practical and cultural barriers of reporting patient safety incidents in three accredited public hospitals in East Java, Indonesia. Methods: This study employed a mixed methods approach using a convergent parallel design. We surveyed 1121 health workers and interviewed 27 managerial staff members from the sampled hospitals. A chi-square analysis was performed to evaluate differences in demographic factors, barriers to reporting, and practices of reporting between those who had repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
1
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 18 publications
0
19
1
12
Order By: Relevance
“…Several studies have identified the barriers that contribute to low incident reporting rates in Indonesian hospitals. [7][8][9] The high prevalence of under-reporting severely undermines the capacity of incident reporting systems to promote learning and improve patient safety. We used previous framework in identifying the factors that lead to patient safety incident reporting that consisted of organizational factors, work environment, process and system of reporting, factors related to patient safety team at hospital level, knowledge and skills of reporting personnel, individual characteristics of health care professionals, professional ethics, fear of adverse consequences, and incident characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified the barriers that contribute to low incident reporting rates in Indonesian hospitals. [7][8][9] The high prevalence of under-reporting severely undermines the capacity of incident reporting systems to promote learning and improve patient safety. We used previous framework in identifying the factors that lead to patient safety incident reporting that consisted of organizational factors, work environment, process and system of reporting, factors related to patient safety team at hospital level, knowledge and skills of reporting personnel, individual characteristics of health care professionals, professional ethics, fear of adverse consequences, and incident characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The patient safety incident reporting system is the monitoring and prevention of injury to patients. The purpose of the reporting system is to learn from mistakes so as to minimize the recurrence of the same mistakes (Samsiah et al, 2016) (M. Christopher, 2016) (Dhamanti, et al, 2020) HCWs play an important role in PSI reporting, but the information is not fully understood. In Malaysia, the number of reported incidents is lower than the actual number of incidents.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, even though the reporting system has been made anonymously, around 45% of nurses are still reluctant to report it (Fathi et al, 2017). In Indonesia, a total of 1,227 hospitals have been accredited, but only 668 incidents were reported in 2016, whereas when compared to Taiwan, every year there are 50.000 incidents reported (Dhamanti, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…20 Perasan takut dihukum, disalahkan, di intimidasi dan dinilai tidak kompeten apabila melaporkan insiden merupakan faktor individu yang menghambat pelaporan insiden di rumah sakit. 10,13,15,17,11,18,19…”
unclassified
“…10 Sampel terkecil terdapat pada penelitianPeyrovi et al (2016) yang dilakukan di Rumah Sakit Pendidikan di Provinsi Kurdistan dan Teheran, Iran, dengan total sampel sebanyak 16. 11 Sebagian besar artikel diterbitkan dalam jurnal internasional yang terindeks PubMed dan ScienceDirect.…”
unclassified